Manufacturing Employment and Women's Agency: Evidence from Lesotho 2004-2014 - Louise Grogan (Institute of Labor Economics (IZA), 2022)
This paper examines the impact of manufacturing employment on women's health and decision-making power within households in Lesotho. Under the US African Growth and Opportunity Act of 2000, the employment of women in ready-made garment (RMG) factories in new industrial zones greatly increased. Subsequent shocks to international demand for textile products created by the phase-out of the Multi-Fiber Agreement and the 2008 Financial Crisis temporarily reduced well-paid RMG work opportunities. Women residing closer to the industrial zones were particularly affected. These changes are exploited for identification of causal impacts. Employment in the RMG sector is found to substantially increase women's say in decisions about the allocation of household resources and own health.
Keywords: J13; J12; P0; P13; 330; Lesotho; manufacturing; trade; Africa Growth and Opportunities Act (AGOA); Demographic and Health Surveys; IPUMS census; World Bank Enterprise Surveys; Multiple Indicator Cluster Surveys (MICS); female labour supply; contraceptives; fertility; autonomy